Currículo da educação do campo no município de Palmas-TO: concepção e organização pedagógica no ensino fundamental - Santos, Daniel Barbosa dos (Universidade Federal do Tocantins, 2023)
The present research focuses on the curriculum policy of rural schools that offer elementary education in the municipality of Palmas-TO. The research starts from the following question: are the curricula of rural schools in the municipality of Palmas-TO, which offer elementary education, adequate to meet the specificities of rural education?In this sense, the general objective of the work is to apprehend the concept of rural education that guides the elementary school curriculum of rural schools in the municipal education system of Palmas-TO. The specific objectives are: to systematize the theoretical-conceptual, political debate and the legal contribution that support the curricular guidelines for rural elementary education in Brazil; to identify the construction process and the guiding conceptions of the guidelines and goals of the curricular policy for elementary education in the countryside in the municipal education system of Palmas-TO; to characterize the offer of rural education in the municipal education system of the municipality of Palmas-TO; to analyze, in the light of the theoretical framework and the Political-Pedagogical Projects, the political-pedagogical assumptions that guide the elementary school curriculum of the five schools in the countryside of the municipality of Palmas-TO. to apprehend from the historical context of Education in Campo de Palmas-TO to the proposals for curricular adaptation to the peculiarities of rural populations, from a qualitative approach to the data. Preliminary results indicate that the curricular proposal in four rural schools does not differ from the curriculum of urban schools and that only one is in accordance with the adaptation to the physical structure of functioning, with the contents and the curricular organization. The other schools are out of step with the Operational Guidelines for Rural Education. In this way, the study identifies that the curricular proposal for the rural school in the municipality has not taken into account the appreciation of local identity and still remains the introduction of an urban school content, which, at times, is prioritized in the curriculum and leaves the construction of knowledge of the local culture in anonymity. In this aspect, we question the need for a specific curricular proposal, with subjects with content aimed at the teaching of the peasant population, which ensures and values the differences in the teaching models of the countryside.